Encapsulation of Explant-Derived Cardiac Stem Cells in Agarose Nanoporous Gel Cocoons to Enhance Cardiac Repair - Kanda, Pushpinder (Université d'Ottawa / University of Ottawa, 2019)
Micro-encapsulation of heart explant-derived stem cells (EDCs) within protective nanoporous gel (NPG) cocoons improves cardiac function and long-term retention of transplanted cells after ischemic injury by limiting detachment induced cell death and vascular clearance of intramyocardial injected cells. Although cocooned EDCs boost cardiac function, the fundamental mechanism is unclear. Here, we investigate the effects of altering cocoon stiffness and size on human EDC mediated repair of damaged myocardium using an immunodeficient mouse model of ischemic cardiomyopathy. First, we found that increasing cocoon stiffness by altering NPG content boosted cell viability and migration; effectively forcing cocooned cells to adopt a migratory, invasive phenotype. Although cocooning improved retention of transplanted cells, increasing cocoon stiffness had no additional effects on long-term engraftment despite markedly improving cardiac function and fibrosis after myocardial infarction. Given increased cocoon stiffness boosted the production and microRNA cargo within EDC nanovesicles, the observed benefits in post-ischemic function are likely dependent more on paracrine production of transplanted cells rather than simply increasing the number of cells retained. The effect of cocoon diameter on EDC phenotype and cell mediated repair of ischemic myocardium was evaluated using microfluidic-based cocooning enabling deterministic encapsulation within defined cocoon size and intracapsular cell number while maintaining a fixed cocoon stiffness. Increased cocoon size enhanced post-ischemic cardiac function by reducing clearance of transplanted cells and increased paracrine stimulation of endogenous repair. The latter being attributable to microfluidic cocooning closely following the expected Poisson distribution with smaller cocoons having a greater proportion of single cells while larger cocoons contained greater proportions of multicellular aggregates which enhanced cell-cell interactions to increase the amount and breadth of cytokines/nanoparticles delivered to injured myocardium. In conclusion, altering the biophysical properties of NPG surrounding cocooned cells provides a straightforward means of boosting the regenerative potential of heart EDCs for repair of injured myocardium.
Keywords: Stem cell; Cardiac repair; Ischemic cardiomyopathy; Microfluidic; Encapsulation; Heart failure; Nanoporous gel; Exosome